Bilitis. Między tekstem pornograficznym a tekstem lesbijskim - Skucha, Mateusz (Śląskie Studia Polonistyczne, 2019)
The article is devoted to The Songs of Bilitis, published at the end of 19th century in France by Pierre Louÿs, who posed as a discoverer and translator of ancient pieces by a beloved Sappho’s apprentice, but in fact authored them. The songs are divided into three parts. In the initial one, Bilitis is a young girl discovering for the first time her corporeality and sexuality. In part two, she resides in the island of Lesbos and is in a fulfilling/happy relationship with Mnasidika. In part three, she is in Cyprus as a temple courtesan. Ramifications of the mentioned literary forgery are a key point here, namely: What occurs in literary (and lovers’) communication if one assumes the authorship by a women or, conversely – if we assume a male authorship.